The Role of Educational Leaders in Enhancing Educational Transformation - Kamara, Yusufu; Burhanuddin, Burhanuddin (Faculty of Education Universitas Negeri Malang, 2025)
This research explored how educational leaders contribute to educational transformation including university leaders, school principals, policymakers, and administrators. This study focused on identifying leadership qualities, strategies for innovation, and methods for overcoming challenges in achieving sustainable change in the educational sector. The study employed a qualitative method where the documents, articles, books, and official statements related to this research were analyzed to get reliable data. Educational transformation is essential to meet the demands of an ever-evolving global landscape, that requires a shift from traditional practices to more dynamic, inclusive, and future-ready approaches. This research work explores the critical role of educational leaders in driving and sustaining transformative change within educational systems. As key agents of change, educational leaders as well as administrators, policymakers, and institutional heads play a central role in reimagining curricula, fostering innovation, and promoting a culture of continuous improvement. Through literature review, the research highlights successful strategies and leadership practices that have facilitated impactful educational transformation across various contexts. The findings emphasize the necessity of visionary leadership to build resilient educational systems capable of adapting to social, economic, and technological shifts. This study provides actionable insights for policymakers, educators, and leadership development programs, contributing to the broader discourse on creating innovative and equitable learning environments for the future.